Facile synthesis of 2D nitrogen-containing porous carbon nanosheets induced by graphene oxide for high-performance supercapacitors. Issue 11 (7th August 2018) - Zhang, Xu; Fan, Qiuyu; Zhao, Yingyuan; Wang, Man; Meng, Yulan; Xiao, Yonghou; Lei, Xiaoting; Yang, Juan
Abstract : 2D N-containing porous carbon nanosheets are prepared in the presence of GO as a structure-directing agent by a facile hydrothermal method. Abstract : Two-dimensional (2D) nitrogen-containing porous carbon nanosheets are prepared in the presence of graphene oxide (GO) as a structure-directing agent by a simple yet facile hydrothermal method. It is found that GO can effectively tune the morphologies of the hydrothermal carbonaceous products, resulting in the unique 2D structures. The as-obtained 2D nitrogen-containing porous carbon nanosheets as electrodes for supercapacitors exhibit a high specific capacitance of 301.6 F g −1 at a current density of 0.5 A g −1 and superior rate capability with a capacitance retention of 70.5% at a high current density of 20 A g −1 . The 2D nitrogen-containing porous carbon nanosheet electrodes also exhibit good cycling performance, possessing a high capacitance retention of over 92.3% after 5000 charge–discharge cycles at a current density of 5 A g −1 . Such superior electrochemical performance of the 2D nitrogen-containing porous carbon nanosheets could be attributed to the high pseudocapacitive effect of the nitrogen-containing species and the peculiar structural characteristics featuring a short ion transport distance and abundant porous channels.